2018
DOI: 10.1101/249524
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcription-dependent DNA methylation at the imprintedZrsr1-DMR

Abstract: Zrsr1 is a paternally expressed imprinted gene located in the first intron of Commd1, and the Zrsr1 promoter resides in a differentially methylated region (DMR) that is maternally methylated in the oocyte. However, a mechanism for the establishment of the methylation has remained obscure. Commd1 is transcribed in the opposite direction to Zrsr1 with predominant maternal expression, especially in the adult brain. In this study, we found Commed1 transcribed through the DMR in the growing oocyte. Zrsr1-DMR methyl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…Notably, we observed increased expression of Dnmt3l, a coactivator of Dnmt3a and Dnmt3b, which catalyze de novo DNA methylation 31 . During placental development, Dnmt3l is essential for establishing proper maternal gene imprinting profiles and is highly expressed in trophoblasts [31][32][33] . While the impact of Dnmt3l overexpression on the placenta is unknown, studies have demonstrated morphological defects and abnormal trophoblast patterns in Dnmt3l knockout mice, providing further evidence of its critical role in proper embryonic development 34,35 .…”
Section: Preimplantation Alcohol Exposure Had a Greater Impact On Imp...mentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, we observed increased expression of Dnmt3l, a coactivator of Dnmt3a and Dnmt3b, which catalyze de novo DNA methylation 31 . During placental development, Dnmt3l is essential for establishing proper maternal gene imprinting profiles and is highly expressed in trophoblasts [31][32][33] . While the impact of Dnmt3l overexpression on the placenta is unknown, studies have demonstrated morphological defects and abnormal trophoblast patterns in Dnmt3l knockout mice, providing further evidence of its critical role in proper embryonic development 34,35 .…”
Section: Preimplantation Alcohol Exposure Had a Greater Impact On Imp...mentioning
confidence: 99%
“…During placental development, Dnmt3l is essential for establishing proper maternal gene imprinting profiles and is highly expressed in trophoblasts (Bourc'his et al, 2001;Joh, 2018;Logan et al, 2013).…”
Section: 3preimplantation Alcohol Exposure Had a Greater Impact On Im...mentioning
confidence: 99%